Analysis of Differences in Farmer Income Estimation Between Middlemen and Animeter For Bali Cattle in Jaro Subdistrict, Tabalong Regency, South Kalimantan - Aulia Rakhman, Muhammad Andika; Soeharsono; Al-Arif, Moh. Anam; Lukiswanto, Bambang Sektiari; Triakoso, Nusdianto; Ma'ruf, Anwar (Universitas Airlangga, 2024)
This study investigates differences in farmer income and body weight estimation for male and female Bali cattle in extensive farming in Jaro Subdistrict, Tabalong Regency, South Kalimantan. A random sampling approach was used, involving farmers from nine villages. Statistical analyses revealed a significant difference (p < 0.05) in the body weights of male Bali cattle measured by an animeter compared to those estimated by middlemen. In contrast, no significant difference (p > 0.05) was observed for female Bali cattle. These differences significantly impacted farmer income for male cattle because the income estimated by the animeter exceeded that estimated by the middlemen (p < 0.05). However, no significant difference (p > 0.05) was observed between the two estimation methods for female cattle. In addition, no significant relationship was observed between the estimates made by the middlemen and those made by the animeter for both sexes of Bali cattle. This study used the Monte Carlo simulation to predict demand for male and female Bali cattle in 2024. On average, farmers were able to supply between two and three male Bali cattle and between three to seven female Bali cattle per month. To ensure a steady income, farmers are advised to supply at least one male or female Bali cattle. Moreover, farmer groups are encouraged to compensate for cattle shortages or surpluses, thereby ensuring a stable supply for middlemen and consumers.